Task based learning activities to develop reading comprehension among students of ninth-year “a”, afternoon session at 27 de Febrero high school in the city of Loja during 2019-2020 school year - Santin Bustamante, Kimberly (2020)
This research work aimed to improve reading comprehension through task based learning activities among students of ninth-year “A”, afternoon session at 27 de Febrero High School during the 2019 - 2020 school year. The methods utilized in this research to collect, describe, process, interpret and analyze data were: the scientific, descriptive, statistical, and analytic-synthetic. To collect information about students’ reading comprehension skills, some instruments were employed, such as tests and questionnaires which were applied to twenty-nine students. Observation sheets and reflective journals were also used to record students’ performance and attitude towards task based learning activities. The results showed that students developed significantly their abilities in reading comprehension, such as discovering main idea, identifying supporting details and sequencing events. To conclude, task based learning activities were effective to improve students’ reading comprehension as they guided students to comprehend what they read and raised the desire to participate confidently in lesson.